2016
DOI: 10.3389/fpsyg.2016.00398
|View full text |Cite
|
Sign up to set email alerts
|

The Timing and Effort of Lexical Access in Natural and Degraded Speech

Abstract: Understanding speech is effortless in ideal situations, and although adverse conditions, such as caused by hearing impairment, often render it an effortful task, they do not necessarily suspend speech comprehension. A prime example of this is speech perception by cochlear implant users, whose hearing prostheses transmit speech as a significantly degraded signal. It is yet unknown how mechanisms of speech processing deal with such degraded signals, and whether they are affected by effortful processing of speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 53 publications
4
63
0
Order By: Relevance
“…These findings are in line with R€ onnberg et al 2013, which states that based on the ELU model, additional WMC is important for listeners to understand hearing aid processed speech when matching supposedly is disrupted by low fidelity of the signal. Wagner, Toffanin, and Başkent (2016) studied the impact of degraded speech on lexical access, and they found that lexical processing was more time consuming and effortful when speech was degraded than natural speech. In other words, the deployment of cognitive resources in speech understanding increases as the fidelity of the input signal decreases.…”
Section: Signal Processingmentioning
confidence: 99%
“…These findings are in line with R€ onnberg et al 2013, which states that based on the ELU model, additional WMC is important for listeners to understand hearing aid processed speech when matching supposedly is disrupted by low fidelity of the signal. Wagner, Toffanin, and Başkent (2016) studied the impact of degraded speech on lexical access, and they found that lexical processing was more time consuming and effortful when speech was degraded than natural speech. In other words, the deployment of cognitive resources in speech understanding increases as the fidelity of the input signal decreases.…”
Section: Signal Processingmentioning
confidence: 99%
“…Subsequently, the Event Related Pupil Dilation (ERPD) percentage was computed. This was calculated using the equation in [16]. Some problems with the eye-tracker were experienced during data collection where a warning of the pupil size was shown.…”
Section: Pre-processing Of Pupil Measurementsmentioning
confidence: 99%
“…multitasking). The rationale for including secondary task responses in the silent period following the sentence is that the time course of attention and lexical access extends beyond stimulus presentation (Kahneman, 1973;Wagner et al, 2016).…”
Section: Dual-taskmentioning
confidence: 99%